# Equations » Fractional equations

To solve a fractional equation you have to remove the fraction by multiplying both sides of the equation with the denominator(s).
Important: Check your solutions. Perhaps a solution will not have an outcome in the original equation. See example 4.

Example 1 with the card method

 1202x – 9 = 24 card method: card on 2x – 9 2x – 9 = 5 2x = 14 x = 7

Example 1 with multiplying by the denominator

 1202x – 9 = 24 both sides times (2x – 9) 120 = 24(2x – 9) 120 = 48x – 216 336 = 48x x = 7

Example 2

 3 – 5xx + 3 = –2 both sides times (x + 3) 3 – 5x = –2(x + 3) 3 – 5x = –2x – 6 3 – 5x = –6 –3x = –9 x = 3

Example 3

 x + 13x – 2 = x – 3 both sides times (x – 2) x + 13 = (x – 3)(x – 2) x + 13 = x2 – 5x + 6 –x2 + 6x + 7 = 0 x2 – 6x – 7 = 0 (x + 1)(x – 7) = 0 x = –1 or x = 7

Example 4

 12x + 3 = 3x2x + 6 cross products 12(2x+ 6) = 3x(x + 3) 24x + 72 = 3x2 + 9x –3x2 + 15x + 72 = 0 x2 – 5x – 24 = 0 (x – 8)(x + 3) = 0 x = 8 of x = –3

When we fill in x = –3 into the original equation we will get no outcome because you will get a division by zero. Therefore only x = 8 is the solution.

Example 5

 6x2 – 12x2 – 12 = 0 card method: de numerator must be 0! 6x2 – 12 = 0 6x2 = 12 x2 = 2 x = or x = – Example 6

 xx – 1 + 2x + 1 = 2 both sides times (x – 1) both sides times (x + 1) x + 2(x – 1)x + 1 = 2(x – 1) x(x + 1) + 2(x – 1) = 2(x – 1)(x + 1) x2 + x + 2x – 2 = 2(x2 – 1) x2 + 3x – 2 = 2x2 – 2 –x2 + 3x = 0 –x(x – 3) = 0 x = 0 or x = 3

Example 7

 x2 – 16x2 + 3x – 4 = x20 (x + 4)(x – 4)(x + 4)(x – 1) = x20 x – 4x – 1 = x20 cross products x(x – 1) = 20(x – 4) x2 – x = 20x – 80 x2 – 21x + 80 = 0 (x – 5)(x – 16) = 0 x = 5 or x = 1 6